Pengaruh Rasio Permodalan, Risiko Pembiayaan, Peringkat Good Corporate Governance dan Rentabilitas terhadap Dana Pihak Ketiga pada Bank Umum Syariah di Indonesia Periode 2014 - 2019 - Ali Akbar (Universitas Batanghari Jambi, 2020)
This research is to know the effect of the Capital Ratio (Capital Adequacy Ratio), Financing Risk (Non Performing Financing), Good Corporate Governance Ratings and Earnings (Net Rewards) on Third Party Funds at Sharia Commercial Bank in Indonesia for the period 2014 - 2019. The population in this research amount of 14 Sharia Banks in Indonesia for the period 2014 - 2019 with sample amount of 8 Sharia Banks. The method used is multiple linear regression analysis using the SPSS program or software. The results showed that partially the Capital Adeguacy Ratio has negative and significant effect on Third Party Funds, Non Performing Financing has positive and significant effect on Third Party Funds, the Good Corporate Governance Rating has negative and insignificant effect on Third Party Funds and Net Rewards has positive and not significant on Third Party Funds. While, simultaneously the Capital Adequacy Ratio, Non Performing Financing, Good Corporate Governance and Net Rewards have significant effect on Third Party Funds.